The impact of carrier media physical properties on moving attached growth systems. - Dias, Joana Manuel Silva (Cranfield University, 2018)
Moving attached growth processes are commonly used for the effective removal of organic pollutants and nitrogen in wastewater treatment plants. In these processes, biofilm grows attached to plastic media. Moving attached growth systems, such as submerged aerated filters (SAF), moving bed biofilm reactors (MBBR) and integrated fixed film activated sludge (IFAS), are traditionally designed and operated based on the carrier media protected surface area (PSA). Therefore, much attention has been given to maximising carrier PSA, neglecting other carrier media physical proprieties, such as geometry, size, shape and voidage. This thesis investigated the influence of carrier media physical properties on moving attached growth systems, contributing to improved reactor performance. A pilot plant treating municipal wastewater was operated with five media that varied in shape (cylindrical and spherical), size, voidage and protected surface area (112-610 m²/m³). Hydrodynamic and aeration tests revealed that carrier media enhanced the overall oxygen transfer and hydraulic efficiency (HE) by 23-45% and 41-53%, respectively. A weak correlation was identified between these parameters and carrier media PSA, the variable traditionally selected to design biofilm processes. However strong correlations were identified when considering a combination of carrier media physical parameters; specifically, dimensionality (Di) and voidage (Voi) (R²= 0.88-0.92). When the pilot plant was operated under the same organic (7.52±0.81 g COD/m².day) and ammonia loading rates (0.94±0.10 g NH₄⁺-N/m2.day), start-up studies indicated that spherical and lower PSA (112-220 m²/m³) carrier media achieved faster biofilm formation rates and shorter start-up periods (15-30 days) compared with cylindrical and higher PSA (348-610 m²/m³) carrier media (23-47 days). During steady state, obtainable COD removal and ammonia removal was 87±1.4 and 74±6.1% with spherical media and 85.5±0.5 and 38±5.0% with cylindrical shape media. Heterotrophic and nitrifiers’ activity tests demonstrated that spherical media presented the highest organic removals (19.2-34.8 mg sCOD/g TS.h) while smaller spherical shape media achieved the highest nitrification removals (5.2-7.2 mg NH₄⁺-N/g TS.h) compared to cylindrical shape media (13.4 mg sCOD/g TS.h and 4.9-5.2 mg NH₄⁺ -N/g TS.h). Strong correlations were achieved between biofilm formation rates, maximum COD utilisation rate and ammonia removal rate and the association of parameters (Di x Voi)/HE (R²= 0.92-0.95). Studies on boundary layer thickness (geometry) and external mass transfer helped with the interpretation of these results. The mass transfer boundary layer (MTBL) thickness values were smaller in the spherical media and high voidage media (low PSA) (71.4, 15.5 μm) in comparison with cylindrical media and low voidage media (high PSA) (122.9 μm). Hence, media voidage and shape impacted on MTLB and played a role in reducing mass transfer limitations. Media with high PSA was greatly affected by mass transfer limitations. Poor correlation was observed between PSA and MTBL thickness (R²= 0.27) and stronger correlations were verified with the combination of parameters: (Di x Voi)/HE (R²=0.86). This thesis showed that the traditional indicator used to design and model biofilm processes, PSA, was insufficient to explain the behaviour of moving attached growth systems. Media physical parameters (such as shape, Di and Voi) should be considered when evaluating existing process hydraulic efficiency, oxygen mass transfer, start-up, performance, modelling as well as during the development of new carrier media and design of biofilm processes.
Keywords: Biofilm; biofilm formation rate; biofilm thickness; biofilm activity; boundary layer thickness; carrier media; dimensionality; hydraulic efficiency; moving attached growth systems; oxygen transfer efficiency; protected surface area; start-up; voidage